Bioethics and the epistemological paradigm of complexity - Ρεθυμνιωτάκη (Eleni Rethimiotaki), Ελένη (Bioethica, 2017)
Nearly half a century now, the regulation of biomedical research and its technological applications, particularly in medical practice, takes place through a novel combination of positive sciences with humanities, philosophy and social theory of science. However, their combination is still a challenge both practically and theoretically. The practical challenge is how scientific and technological progress combined to the economic and social development it brings is harmonized with the protection of natural and social goods as well as the respect for individual freedoms. Besides, the regulation of biomedicine consists an epistemological challenge for philosophy and theory of science. The work of the deceased Thanassis Papachristou, Professor of Law School of the National and Kapodistrian University in Athens and a former member of the National Bioethics Committee, has been a pioneer precisely because he perceived the dual challenge being simultaneously a civilist and a sociologist of law. The article explains first the reasons why his work opens up to a dynamic view of the regulation of biomedicine. Second, it proceeds further and after quoting the basic theoretical assumptions of the epistemological example of complexity, it develops arguments in favor of its adoption for the interpretation and description of bioethics with bio-law and their combination in the modern model of regulation of biomedicine. Thirdly, the article exposes some thoughts about the implementation of the complexity paradigm in the case pf the Greek model of regulation of biomedicine and the dynamics of bioethics development within it.